Hollow adsorbent, preparation method thereof and adsorption device

By adopting adsorbents with hollow structures, the problems of poor cycle stability and high water consumption in the existing adsorption methods are solved, and the efficient process of brine lithium extraction is achieved, with excellent adsorption efficiency and low water consumption characteristics.

CN119771374APending Publication Date: 2025-04-08BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411550840.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When the existing adsorption method is used for lithium extraction of brine, the adsorbent has poor circulation stability, low adsorption efficiency, low adsorption utilization rate and high water consumption during the desorption process, which limits the development of lithium extraction of brine.

Method used

A hollow adsorbent is used, which comprises at least one hollow tube body, the inner diameter of the tube body is 0.01-2mm, the length is 0.1-5mm, the wall thickness is 0.02-0.2mm, and the powdering rate is ≤0.5%. The inner and outer diameters and wall thickness of the hollow tube body are within a specific range. Combined with an appropriate amount of adhesive, pore-forming agent and additives, a multi-dimensional pore system is built to improve adsorption performance.

Benefits of technology

The hollow adsorbent exhibits excellent cycle stability, adsorption efficiency and adsorption utilization rate during the lithium extraction process of brine, and the water consumption is low during the desorption process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771374A_ABST
    Figure CN119771374A_ABST
Patent Text Reader

Abstract

The invention provides a hollow adsorbent, a preparation method thereof and an adsorption device, the hollow adsorbent comprises at least one hollow tube body, and the hollow tube body comprises an adsorption material; the wall thickness of the hollow pipe body is 0.02-0.2 mm, and the pulverization rate is smaller than or equal to 0.5%. The hollow adsorbent has excellent cycling stability, adsorption efficiency and adsorption utilization rate, and the water consumption is low when the hollow adsorbent is used for extracting lithium from brine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hollow adsorbent and a preparation method and an adsorption device thereof, belonging to the technical field of adsorbent preparation. Background Art

[0002] Lithium ions are widely used in energy, medical, industrial and scientific research, and are one of the indispensable resources in modern society. Currently, lithium ions are obtained by extracting lithium from brine, which has the advantages of low cost, high environmental protection and high production efficiency. Common methods for extracting lithium from brine include adsorption, solvent extraction, membrane separation and electrochemical methods.

[0003] Among them, the adsorption method refers to the use of specific adsorption materials to selectively adsorb lithium ions in brine, and then desorb the lithium ions from the adsorption material through an eluent to obtain a lithium-rich solution. The currently commonly used eluent is an aqueous solution.

[0004] Although the adsorption method has the advantages of high selectivity and high efficiency, the adsorbents currently used in the adsorption method generally have problems such as poor cycle stability, low adsorption efficiency, low adsorption utilization rate and high water consumption during desorption, which seriously limit the development of lithium extraction from brine by adsorption method. Summary of the invention

[0005] The invention provides a hollow adsorbent, which has excellent cycle stability, adsorption efficiency and adsorption utilization rate and has low water consumption when used for lithium extraction from brine.

[0006] The present invention also provides a method for preparing a hollow adsorbent. The method has a simple process flow, high production efficiency, energy saving and environmental protection, and can prepare the above-mentioned hollow adsorbent.

[0007] The present invention also provides an adsorption device, which includes the above-mentioned hollow adsorbent, so the device has excellent cycle stability, adsorption efficiency and adsorption utilization rate, and has low water consumption when used for lithium extraction from brine.

[0008] In one aspect, the present invention provides a hollow adsorbent, comprising at least one hollow tube, wherein the hollow tube comprises an adsorbent material;

[0009] The wall thickness of the hollow tube is 0.02-0.2 mm, and the powdering rate is ≤0.5%.

[0010] As for the hollow adsorbent as described above, the inner diameter of the hollow tube is 0.01-2 mm, and the length is 0.1-5 mm.

[0011] The hollow adsorbent as described above comprises N hollow tubes which are sequentially nested, 2≤N≤5, and there is a contact area between two adjacent hollow tubes. The arc length of the contact area of ​​the cross section of the hollow tube is L1, and the overall arc length of the cross section of the hollow tube is L2, satisfying L1:L2=5%~50%.

[0012] As for the hollow adsorbent as described above, the inner diameter of the hollow tube is 0.1-0.5 mm, the wall thickness is 0.05-0.2 mm, and the length is 0.5-3 mm.

[0013] The hollow adsorbent as described above, wherein the bulk density of the adsorbent material is 0.4-0.5 g / mL;

[0014] And / or, the D50 of the adsorbent material is 0.01-1 μm.

[0015] The hollow adsorbent as described above has a membrane flux of 100-300 L / (m 2 h).

[0016] The hollow adsorbent as described above, further comprising a pore-forming agent, an additive, and a binder;

[0017] The mass ratio of the adsorbent material to the pore-forming agent is 100:(0.1-3);

[0018] and / or, the mass ratio of the adsorbent material to the additive is 100:(0.05-0.5);

[0019] And / or, the mass ratio of the adsorbent material to the binder is 100:(5-14).

[0020] The hollow adsorbent as described above, wherein the adsorbent material comprises at least one of an aluminum-based adsorbent, a titanium-based adsorbent, and a manganese-based adsorbent;

[0021] And / or, the adhesive comprises at least one of homopolymer polyvinylidene fluoride, copolymer polyvinylidene fluoride, polyether sulfone, and polyvinyl butyral;

[0022] And / or, the pore-forming agent includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol, lithium chloride and sodium chloride;

[0023] And / or, the additive includes at least one of oxalic acid, citric acid, and acetic acid.

[0024] In another aspect, the present invention provides a method for preparing the hollow adsorbent as described above, comprising the following steps:

[0025] 1) subjecting a mixed solution including an adsorbent material and an organic solvent to a first stirring treatment, and then subjecting the mixed solution to a first exhaust treatment to obtain a degassed suspension;

[0026] 2) performing a second stirring treatment on the second mixed liquid including the degassed suspension to obtain a precast membrane liquid;

[0027] 3) vibrating the precasting liquid, and then performing a second vacuuming process to obtain a casting liquid;

[0028] 4) The casting solution is subjected to hollow molding treatment in sequence, and cut to obtain the hollow adsorbent.

[0029] In the preparation method as described above, the second mixed solution further comprises a binder, a pore-forming agent, and an additive;

[0030] The rotation speed of the first stirring treatment is 100-800 rpm;

[0031] And / or, the pressure of the first vacuum treatment is 0.5-4KPa, and the time is 1-2h;

[0032] And / or, the second stirring treatment has a rotation speed of 100-800 rpm and a temperature of 25-80° C.;

[0033] And / or, the frequency of the vibration treatment is 25-100 Hz, and the time is 10-40 s;

[0034] And / or, the pressure of the second vacuum treatment is 0.5-4 KPa, and the time is 1-2 hours.

[0035] The preparation method as described above, wherein the hollow molding process comprises the following steps:

[0036] The filtered casting liquid and core liquid are used to prepare adsorbent filaments by a spinning head. The flow rate ratio of the core liquid to the filtered casting liquid is in the range of (1-10):1, and the air bath height is 5-30 cm. The filaments are then coagulated in a coagulation solvent at 25-80° C. to obtain an intermediate.

[0037] In the preparation method as described above, in step 4), the hollow molding process further includes washing, and the washing includes the following steps:

[0038] The intermediate obtained by the hollow molding treatment is washed with water and then immersed in a 50 wt. % to 70 wt. % glycerol aqueous solution for 2 to 6 hours.

[0039] In another aspect, the present invention provides an adsorption device, comprising the hollow adsorbent as described above or the hollow adsorbent prepared by the preparation method as described above.

[0040] In the adsorption device as described above, the packing density of the hollow adsorbent in the adsorption device is not less than 0.38 g / mL.

[0041] The adsorption device as described above is prepared by a method comprising the following steps:

[0042] The hollow adsorbent is loaded into the cavity of the adsorption device in several batches, and water is passed through the cavity at a flow rate of 10-30 m / s for compaction for 10-30 minutes after each loading.

[0043] As described above, the hollow adsorbent is loaded into the cavity of the adsorption device in 3-5 times.

[0044] The hollow adsorbent provided by the present invention comprises a specific structure, size and pulverization rate, has excellent adsorption efficiency, adsorption utilization rate and cycle stability in the process of lithium extraction from brine, and has a small water consumption for desorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 A photo of the hollow adsorbent provided in Example 1 of the present invention;

[0046] Figure 2 The scanning electron microscope images of the surface of the hollow adsorbent provided in Example 1 of the present invention magnified 50 times and 20,000 times;

[0047] Figure 3 This is a scanning electron microscope image of a cross section of the hollow adsorbent provided in Example 1 of the present invention magnified 50 times;

[0048] Figure 4 This is a photo of the hollow adsorption cross section provided in Example 5 of the present invention. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] In one aspect, the present invention provides a hollow adsorbent, comprising at least one hollow tube, wherein the hollow tube comprises an adsorbent material; the wall thickness of the hollow tube is 0.02-0.2 mm, and the pulverization rate is ≤0.5%.

[0051] The hollow adsorbent may include one hollow tube or multiple hollow tubes. When the hollow adsorbent includes multiple hollow tubes, the cross-sectional shape of the hollow adsorbent is similar to a concentric circle shape.

[0052] The wall thickness in the present invention refers to the average thickness of each hollow tube. For example, when the hollow adsorbent includes three hollow tubes, the wall thickness refers to the average thickness of each hollow tube.

[0053] The wall thickness of the hollow tube can be measured by a common dimensional testing method in the art, for example, using a scanning electron microscope to test the wall thickness at multiple locations of the cross section of the hollow adsorbent and taking the average value of the test data at multiple locations.

[0054] The pulverization rate of the present invention refers to the ratio of the amount of powder generated by the hollow adsorbent due to physical or chemical effects during use to the initial mass. The pulverization rate test method of the present invention is as follows: take two 500±50g samples, place them on a 60-mesh sieve respectively, pre-screen them on a vibrating sieve machine for 5 minutes, weigh two samples (m1) of 400g±50g from the sieve, and load them into two rotary boxes of the pulverizer respectively, cover the box cover tightly, start the machine, and rotate the box body at a speed of 50 rpm for 500 revolutions. After stopping the machine, take out the sample, place it on a 60-mesh sieve, and sieve the particles on the vibrating sieve machine for 5 minutes. Calculate the percentage of the mass m2 of the sieve (the powder contained in the particles) to m1, which is the pulverization rate.

[0055] The pulverization rate of the hollow adsorbent provided by the present invention is ≤0.5%, which means that the hollow adsorbent is not easily worn or disintegrated during use, can maintain high structural stability and less dust generation, and represents that the hollow adsorbent has excellent cycle stability.

[0056] It is understandable that in order to improve the structural stability and adsorption effect of the hollow adsorbent, the hollow adsorbent also includes a binder, a pore-forming agent, and an additive.

[0057] The hollow adsorbent provided by the present invention has high adsorption efficiency and adsorption utilization rate, and the water consumption in the analysis process is low. The inventors have analyzed this and believe that the reason may be: on the one hand, when the inner diameter, wall thickness and length of the hollow tube body are within a specific range, when the hollow adsorbent is used, the distance between the brine, the eluent, the desorbent and the adsorbent innermost adsorbent material can be shortened, the diffusion range of adsorption, elution and analysis can be reduced, and the time consumption of elution and analysis can be reduced. On the other hand, by constructing a specific microporous system in the adsorbent, the mass transfer rate can be increased, the elution and analysis efficiency can be improved, and the water consumption in the elution and desorption process can be reduced.

[0058] Furthermore, in a specific embodiment of the present invention, the inner diameter of the hollow tube is 0.01-2 mm, and the length is 0.1-5 mm.

[0059] When the hollow adsorbent includes a hollow tube, the inner diameter of the hollow tube is the average diameter of the inner cavity.

[0060] When the hollow adsorbent includes a plurality of hollow tubes, the inner diameter of the hollow tube refers to the diameter of the cavity formed by the inner surface of each hollow tube. It can be understood that the inner diameter of the hollow tube close to the inner cavity is smaller than the inner diameter of the hollow tube close to the surface, the minimum inner diameter of the plurality of hollow tubes is not less than 0.01 mm, and the maximum inner diameter of the plurality of hollow tubes is not greater than 2 mm.

[0061] The length of the hollow adsorbent of the present invention refers to the average length. The length and inner diameter of the hollow tube can be measured by the common size testing methods in the art, for example, using a scanning electron microscope to test the inner diameter of the hollow adsorbent at multiple locations on the cross section and taking the average value of the test data at multiple locations.

[0062] Furthermore, in a specific embodiment of the present invention, the hollow adsorbent includes N hollow tubes arranged in sequence, 2≤N≤5, there is a contact area between two adjacent hollow tubes, the arc length of the contact area of ​​the hollow tube cross section is L1, and the overall arc length of the hollow tube cross section is L2, satisfying L1:L2=5%~50%.

[0063] Among them, during the forming process, two adjacent layers of tube walls of two adjacent hollow tube bodies are partially in contact with each other and partially have obvious gaps.

[0064] L1 and L2 can be detected by scanning electron microscope. In order to improve the accuracy of the value, multiple cross sections can be tested and the average value of the multiple cross sections can be taken. In detail, L1:L2 includes but is not limited to 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or any range between them.

[0065] The present invention does not limit the maximum cross-sectional distance between two adjacent hollow tubes. In a specific embodiment, the maximum cross-sectional distance L between two adjacent hollow tubes is 1 mm.

[0066] When the hollow adsorbent includes multiple hollow tubes, the packing density of the hollow adsorbent and the contact time with the fluid can be effectively increased, and the adsorption rate and adsorption per unit volume of the hollow adsorbent can be improved. By flattening the multi-layer hollow adsorbent in situ in the adsorption column, the adsorption performance of the adsorbent remains unchanged, while the packing density is further improved, and the adsorption performance per unit volume is also greatly improved.

[0067] Furthermore, in a specific embodiment of the present invention, the inner diameter of the hollow tube is 0.1-0.5 mm, the wall thickness is 0.05-0.2 mm, and the length is 0.5-3 mm.

[0068] In detail, the inner diameter of the hollow tube includes but is not limited to 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm or a range between any two of them.

[0069] The wall thickness includes, but is not limited to, 0.05 mm, 0.08 mm, 0.10 mm, 0.12 mm, 0.14 mm, 0.16 mm, 0.18 mm, 0.20 mm or a range between any two of them.

[0070] The length includes but is not limited to 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm or a range between any two thereof.

[0071] When the inner diameter, wall thickness and length of the hollow tube are within the above ranges, the hollow adsorbent has a better adsorption rate, adsorption utilization rate, cycle stability and lower water consumption.

[0072] Furthermore, in one embodiment of the present invention, the bulk density of the adsorbent material is 0.4-0.5 g / mL.

[0073] The bulk density of the adsorbent material refers to the mass of the adsorbent per unit volume of the hollow adsorbent. Specifically, the volume (V) occupied by the adsorbent can be calculated by measuring the outer diameter, inner diameter and length of the hollow adsorbent, and then the dry weight of the adsorbent can be measured by drying. The mass (m) of the adsorbent can be calculated based on the proportion of the adsorbent, and finally calculated by m / V.

[0074] Specifically, the bulk density of the adsorbent material includes but is not limited to 0.4 g / mL, 0.41 g / mL, 0.42 g / mL, 0.43 g / mL, 0.44 g / mL, 0.45 g / mL, 0.46 g / mL, 0.47 g / mL, 0.48 g / mL, 0.49 g / mL, 0.5 g / mL or a range composed of any two thereof.

[0075] When the stacking density of the adsorbent material is within the above range, the hollow adsorbent has more excellent adsorption performance and cycle stability. The inventors analyzed this and believed that the reason may be: on the one hand, the above stacking density provides more adsorbent material per unit volume, thereby improving the adsorption capacity per unit volume and space utilization. On the other hand, the higher the stacking density, the more uniform and dense the microscopic pores inside the adsorbent particles, thereby improving the adsorption, elution and analysis efficiency of the adsorbent, while reducing the powderization rate of the adsorbent and improving its cycle stability in practical applications.

[0076] Furthermore, in a specific embodiment of the present invention, the D50 of the adsorbent material is 0.01-1 μm.

[0077] The adsorbent material of the present invention may be in the shape of flakes, spheres, quasi-spheres, etc. D50 refers to the equivalent average particle size of the adsorbent material.

[0078] In detail, the D50 of the adsorbent material includes but is not limited to 0.01 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm or a range composed of any two thereof.

[0079] When the D50 of the adsorbent material is within the above range, it can ensure that within a certain range of wall thickness, inner diameter and length, the packing density of the adsorbent material is within an appropriate range, further ensuring that the hollow adsorbent has higher adsorption efficiency, adsorption utilization rate, cycle stability and lower water consumption.

[0080] Furthermore, in one embodiment of the present invention, the membrane flux of the hollow adsorbent is 100-300 L / (m 2 h).

[0081] The membrane flux of the hollow adsorbent refers to the volume of liquid passing through the membrane per unit time. It can be obtained by first making the hollow adsorbent membrane filament into a membrane assembly, then passing 0.1MPa pure water through the inner hole, and measuring the water flow rate on the outside of the membrane assembly, and then calculating the flow rate / surface area of ​​the membrane filament.

[0082] In detail, the membrane flux of the hollow adsorbent includes but is not limited to 100L / (m 2 ·h)、120L / (m 2 ·h)、140L / (m 2 ·h)、160L / (m 2 ·h)、180L / (m 2 ·h)、200L / (m 2 ·h)、220L / (m 2 ·h)、240L / (m 2 ·h)、260L / (m 2 ·h)、280L / (m 2 ·h)、300L / (m 2 h) or a range between any two of them.

[0083] When the membrane flux of the hollow adsorbent is within the above range, the adsorption, elution and desorption rates of the adsorbent will be greatly improved, the adsorption amount will be increased, the water consumption will be reduced, and the production capacity of the unit adsorbent will be ultimately increased.

[0084] The hollow adsorbent provided by the present invention was detected by scanning electron microscopy, and it was found that the hollow adsorbent provided by the present invention has abundant internal channels, wherein the mesopores on the outer surface, the finger-like holes penetrating the hollow adsorbent, and the microporous gaps outside the adsorbent particles constitute a multi-dimensional channel system of the hollow adsorbent.

[0085] Furthermore, in a specific embodiment of the present invention, the hollow adsorbent also includes a pore former, an additive, and an adhesive; the mass ratio of the adsorbent material to the pore former is 100:(0.1-3); the mass ratio of the adsorbent material to the additive is 100:(0.05-0.5); the mass ratio of the adsorbent material to the adhesive is 100:(5-14).

[0086] The mass ratio of various components in the hollow adsorbent can be controlled by the addition amount of each raw material during preparation.

[0087] In detail, the mass ratio of the adsorbent to the pore-forming agent includes but is not limited to 100:0.1, 100:0.5, 100:1.0, 100:1.5, 100:2.0, 100:2.5, 100:3.0 or a range between any two of them; the mass ratio of the adsorbent to the additive includes but is not limited to 100:0.05, 100:0.1, 100:0.15, 100:0.2, 100:0.25, 100:0.3, 100:0.35, 100:0.4, 100:0.45, 100:0.5 or a range between any two of them; the mass ratio of the adsorbent to the adhesive includes but is not limited to 100:5, 100:8, 100:10, 100:12, 100:14 or a range between any two of them.

[0088] The mass relationship of various components in the hollow adsorbent can be adjusted by controlling the mass relationship of the raw materials during the preparation process. Among them, the appropriate amount of binder ratio can enhance the strength of the adsorbent particles and reduce the powdering rate while ensuring the proportion of the adsorbent material, while the appropriate amount of pore-forming agent helps to increase the water flux of the adsorbent material while ensuring the strength of the material. At the same time, a small amount of additives can shape the pore structure of the membrane, and a reasonable ratio of these components can help improve the overall performance of the adsorbent.

[0089] Furthermore, in a specific embodiment of the present invention, the adsorbent material includes at least one of an aluminum-based adsorbent, a titanium-based adsorbent, and a manganese-based adsorbent; and / or the binder includes at least one of homopolymer polyvinylidene fluoride, copolymer polyvinylidene fluoride, polyether sulfone, and polyvinyl butyral ester; and / or the pore-forming agent includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol, lithium chloride, and sodium chloride; and / or the additive includes at least one of oxalic acid, citric acid, and acetic acid.

[0090] In another aspect, the present invention provides a method for preparing the hollow adsorbent as described above, comprising the following steps:

[0091] 1) subjecting a mixed solution including an adsorbent material and an organic solvent to a first stirring treatment, and then subjecting the mixed solution to a first exhaust treatment to obtain a degassed suspension;

[0092] 2) performing a second stirring treatment on the degassed suspension to obtain a precast membrane solution;

[0093] 3) vibrating the precasting liquid, and then performing a second vacuuming process to obtain a casting liquid;

[0094] 4) The casting solution is subjected to hollow molding treatment in sequence, and cut to obtain the hollow adsorbent.

[0095] In detail, in step 1), the adsorbent material and the organic solvent are mixed to obtain a suspension, which is then stirred. When the adsorbent material and the organic solvent are fully mixed, a first air extraction process is performed to remove bubbles in the suspension to obtain a degassed suspension.

[0096] In the present invention, the adsorbent material is a hydrophilic material, the solvent used is amphiphilic, and the binder is a hydrophobic material. The hydrophilic adsorbent material is first added to the solvent, so that the adsorbent material can be fully dispersed, thereby avoiding the adsorbent material from forming powder clumps, and is also conducive to the degassing treatment of the system.

[0097] The present invention does not limit the specific type of organic solvent, and can select any organic solvent commonly used in the art, such as at least one of N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, tetrahydrofuran, methyl ethyl acetone and dimethyl sulfoxide.

[0098] In a specific embodiment, the mass ratio of the adsorbent material to the organic solvent is (30-60):100. Specifically, the mass ratio of the adsorbent material to the organic solvent includes but is not limited to 30:100, 35:100, 40:100, 45:100, 50:100, 55:100, 60:100 or a range between any two of them.

[0099] In step 2), a certain amount of binder, pore former and additive are added to the degassed suspension, and the mixture is stirred until uniformly mixed to obtain a precast membrane solution.

[0100] In one specific embodiment, the stirring temperature is 60-80°C.

[0101] A suitable stirring time can be selected according to actual conditions. In a specific implementation, the stirring time is 6 to 12 hours.

[0102] In step 3), the precasting liquid is vibrated, and then a second air extraction process is performed to remove bubbles in the precasting liquid to obtain a casting liquid.

[0103] The combined degassing method of vacuum degassing of the suspension and vibration degassing followed by vacuum degassing of the precast membrane liquid greatly reduces the difficulty of degassing the casting membrane liquid, improves the degassing efficiency, and significantly reduces the bubble porosity in the adsorption material, which not only reduces the difficulty of subsequent hollow molding processing, but also can effectively increase the stacking density.

[0104] In step 4), the casting solution is subjected to hollow molding treatment in sequence and cut to obtain a hollow adsorbent.

[0105] The casting liquid can also be filtered before the hollow molding process. In a specific embodiment, the casting liquid is filtered using a filter to remove large particles of impurities in the casting liquid. The present invention does not limit the number of meshes of the filter used during the filtering process, and a suitable filter can be selected according to actual conditions, such as a 100-350 mesh filter.

[0106] The filtered casting solution is hollow molded to obtain an intermediate with a cavity.

[0107] The preparation method provided by the present invention can prepare a hollow adsorbent with a specific size and pulverization rate. The inventor analyzed this and believed that the reason may be: on the one hand, the preparation method not only uses a large amount of organic solvent to dissolve in the solidification process to form pores, but also uses a pore-forming agent to form a large number of finger-shaped pores, and also uses additives to increase the membrane flux, so that the internal pores of the hollow adsorbent are rich, and the mesopores on the outer surface, the finger-shaped pores running through the hollow adsorbent and the micropore gaps outside the adsorbent particles constitute a multi-dimensional pore system of the hollow adsorbent, which greatly improves the mass transfer rate and lithium extraction efficiency of brine, and reduces the water consumption of elution; on the other hand, the solvent and the adsorbent material are first mixed into a suspension, and then the binder is added to the mixture, which allows the adsorbent material to be mixed very evenly in the suspension, avoiding the appearance of adsorbent material powder clumps that are difficult to disperse in the casting liquid due to the different hydrophilicity of the adsorbent material and the binder, greatly improving the adhesion between the adsorbent particles, significantly reducing the pulverization rate of the hollow adsorbent, and improving the cycle stability.

[0108] Furthermore, in a specific embodiment of the present invention, the second mixed liquid also includes a binder, a pore-forming agent, and an additive; the rotation speed of the first stirring treatment is 100-800rpm; the pressure of the first vacuum treatment is 0.5-4KPa, and the time is 1-2h; the rotation speed of the second stirring treatment is 100-800rpm, and the temperature is 25-80°C; the frequency of the vibration treatment is 25-100Hz, and the time is 10-40s; the pressure of the second vacuum treatment is 0.5-4KPa, and the time is 1-2h.

[0109] Specifically, the rotation speed of the first stirring treatment includes but is not limited to 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm or a range between any two of them; the pressure of the first exhaust treatment includes but is not limited to 0.5kPa, 1kPa, 1.5kPa, 2kPa, 2.5kPa, 3kPa, 3.5kPa, 4kPa or a range between any two of them, and the time includes but is not limited to 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h or a range between any two of them; the frequency of the vibration treatment includes but is not limited to 25Hz, 30Hz, 40Hz, 50Hz, 60Hz, 70Hz, 80Hz, 90Hz, 100Hz or a range between any two of them, and the time includes but Not limited to 10s, 20s, 30s, 40s or any range therebetween; the rotation speed of the second stirring treatment includes but is not limited to 100rpm, 200rpm, 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm or any range therebetween; the temperature includes but is not limited to 25℃, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃ or any range therebetween; the pressure of the second vacuum treatment includes but is not limited to 0.5kPa, 1kPa, 1.5kPa, 2kPa, 2.5kPa, 3kPa, 3.5kPa, 4kPa or any range therebetween, and the time includes but is not limited to 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h or any range therebetween.

[0110] When the parameters in the preparation process are within the above ranges, the various components in the casting solution can be mixed more evenly, further improving the cycle stability, adsorption efficiency and adsorption utilization rate of the hollow adsorbent.

[0111] Furthermore, in a specific embodiment of the present invention, the hollow molding process is a spinning process, comprising the following steps: using a spinning head to prepare adsorbent filaments from the filtered casting liquid and core liquid, the flow rate ratio range of the core liquid and the filtered casting liquid is (1 to 10): 1, the air bath height is 5-30 cm, and then coagulation treatment is carried out in a coagulation solvent at 25-80°C to obtain an intermediate.

[0112] The core liquid mainly includes water, and the solidification solvent includes water or an aqueous solution of an organic solvent. The core liquid can solidify the inner wall of the hollow adsorbent and adjust the inner diameter and inner surface micropores of the hollow adsorbent. The solidification solvent can solidify the hollow adsorbent and affect the microscopic pore structure of the hollow adsorbent.

[0113] The intermediate obtained by hollow molding is washed and then cut. The present invention does not limit the specific device and operation of cutting. In a specific embodiment, a cutting machine is used to cut the intermediate into hollow adsorbents of a certain length.

[0114] Furthermore, in a specific embodiment of the present invention, in step 4), washing is also included after the hollow molding treatment, and the washing includes the following steps: washing the intermediate obtained by the hollow molding treatment with water, and then soaking it in a 50wt.%-70wt.% glycerol aqueous solution for 2-6h to obtain a hollow adsorbent.

[0115] To ensure the washing effect, an aqueous solution and a glycerol aqueous solution of appropriate mass can be selected for washing treatment. For example, an aqueous solution of equal mass to the intermediate and a glycerol aqueous solution of equal mass can be selected for soaking treatment.

[0116] Washing the intermediate obtained by hollow molding can remove soluble impurities and unreacted chemicals on the surface and inside of the intermediate, and remove residues that may affect the performance of the adsorbent. Soaking with 50wt.%-70wt.% glycerol aqueous solution can maintain the structure of the hollow adsorbent, avoid the reduction of membrane flux caused by the shrinkage of the pores of the hollow adsorbent during the drying process, and further activate the adsorbent surface, thereby avoiding the reduction of adsorption efficiency and adsorption performance.

[0117] In another aspect, the present invention provides a treatment method, including the hollow adsorbent as described above or the hollow adsorbent prepared by the preparation method as described above.

[0118] The present invention does not limit the specific type of the adsorption device, and a suitable adsorption device, such as an adsorption column, can be selected according to actual conditions.

[0119] The hollow adsorbent obtained using this in-situ treatment method has excellent adsorption efficiency, adsorption utilization, cycle stability and low water consumption.

[0120] Furthermore, in a specific embodiment of the present invention, the packing density of the hollow adsorbent in the adsorption device is not less than 0.38 g / mL.

[0121] In detail, the packing density of the hollow adsorbent in the adsorption device refers to the mass of the adsorbent particles packed per unit volume, which can be determined by filling a certain volume (V) of adsorbent in a measuring cylinder and weighing the dry weight (m) of the adsorbent, and then determining it by m / V.

[0122] When the packing density of the hollow adsorbent in the adsorption device is increased, a larger adsorption amount per unit volume is provided, thereby improving the adsorption capacity, and can reduce the flow resistance of the fluid when passing through the adsorbent, thereby improving operating efficiency. At the same time, the hollow adsorbent has better mechanical strength and stability, reducing the risk of damage during operation and improving cycle stability.

[0123] Furthermore, in a specific embodiment of the present invention, the adsorption device is prepared by a method comprising the following steps: the hollow adsorbent is loaded into the cavity of the adsorption device in several times, and after each loading, water is passed through at a flow rate of 10-30 m / s for compaction for 10 minutes.

[0124] The hollow adsorbent can be divided into several portions according to actual conditions, and the mass of each portion can be the same or different. In a specific embodiment, the hollow adsorbent is evenly divided into several portions for filling.

[0125] The flow rate of water compaction includes but is not limited to 10 m / s, 15 m / s, 20 m / s, 25 m / s, 30 m / s or a range between any two of them.

[0126] The final flattening and forming is carried out by compacting the hollow adsorbent in situ in the adsorption device, which greatly improves the packing density of the hollow adsorbent and overcomes the problem of too large filling gaps of the hollow adsorbent caused by filling after flattening, further ensuring the adsorption efficiency and utilization rate and reducing water consumption.

[0127] Furthermore, in a specific embodiment of the present invention, the hollow adsorbent is loaded into the cavity of the adsorption device in 3-5 batches.

[0128] When the hollow adsorbent is loaded into the cavity of the adsorption device in 3-5 times, it can not only overcome the problem of too large filling gap of the hollow adsorbent caused by flattening and then loading, but also ensure a certain filling efficiency.

[0129] Hereinafter, the hollow adsorbent and adsorption device provided by the present invention are introduced through specific embodiments.

[0130] Example 1

[0131] The preparation method of the hollow adsorbent and the adsorption device provided in this embodiment comprises the following steps:

[0132] 1) Add aluminum-based adsorbent (D50 is 0.5 μm) and N-methylpyrrolidone into a reaction kettle at a mass ratio of 1:2, mix them thoroughly at room temperature to obtain a mixed solution, stir them at a stirring rate of 800 rpm, and evacuate them at 2 kPa for 1 h to obtain a degassed suspension;

[0133] 2) Add polyvinylidene fluoride (molecular weight of 700,000-1.2 million), polyvinyl pyrrolidone (molecular weight of 5,000-40,000), and oxalic acid to the degassed suspension in a mass ratio of 10:100, 1.5:100, and 0.2:100 to the adsorbent material, respectively; stir at 80°C and 800 rpm until completely dissolved to obtain a precast membrane solution;

[0134] 3) Degas the precasting liquid by vibrating it at a frequency of 50 Hz for 30 seconds, and then degas it under vacuum at 2 kPa for 1 hour to obtain a casting liquid;

[0135] 4) Pump the casting liquid through a 200-mesh filter to filter out large particles of impurities in the casting liquid, and then spin the adsorbent filaments through a spinning head. The spinning head temperature is 60°C, and water is introduced in the middle as the core liquid. The flow rate ratio of the core liquid and the spinning is 1:1. The air bath height is 30cm. The filaments are single-hole circular tubes with an inner diameter of 0.3mm and a wall thickness of 0.1mm. The spun filaments are solidified in 60°C water, and the membrane filaments are washed five times with an equal mass of water, and then soaked in a 50% glycerol aqueous solution for 2 hours. Cut the adsorbent filaments into particles to obtain a hollow adsorbent with an inner diameter of 0.3mm, a wall thickness of 0.1mm, and a length of 1mm with a hollow tube body. Figure 1 This is a photo of the hollow adsorbent.

[0136] 5) Load the hollow adsorbent into the empty adsorption column in 5 times, flush it with water from top to bottom at a speed of 10m / s for 30min each time, compact and flatten the hollow adsorbent to obtain the adsorption column.

[0137] The hollow adsorbent provided in this embodiment was tested by scanning electron microscopy, wherein Figure 2 For surface test images magnified 50 times and 20,000 times, Figure 3 This is a test picture of the hollow adsorbent cross section magnified 50 times. Figure 2 It shows that the surface of the adsorbent provided by the present invention is full of micropores, which is conducive to the diffusion of brine, eluent and desorbent. Figure 3 It can be seen that the hollow adsorbent provided by the present invention has abundant internal pores, and the mesopores on the outer surface, the finger-like pores penetrating the hollow adsorbent, and the micropores outside the adsorbent particles constitute a multi-dimensional pore system of the hollow adsorbent.

[0138] After testing, the membrane flux of the hollow adsorbent provided in this embodiment is 300L / (m 2 h).

[0139] Example 2

[0140] The preparation method of the hollow adsorbent and adsorption device provided in this embodiment is basically the same as that in embodiment 1, except that:

[0141] In step 2), the mass ratio of polyvinyl pyrrolidone to the adsorbent material is 3:100; a hollow adsorbent having an inner diameter of 0.3 mm, a wall thickness of 0.1 mm, and a length of 1 mm and a hollow tube is obtained.

[0142] After testing, the membrane flux of the hollow adsorbent with a hollow tube provided in this embodiment is 285L / (m 2 h).

[0143] Example 3

[0144] The preparation method of the hollow adsorbent and adsorption device provided in this embodiment is basically the same as that in embodiment 1, except that:

[0145] In step 4), the distance between the inner wall and the outer wall of the spinning head set by the hollow molding process is 0.25 mm, and a hollow adsorbent with an inner diameter of 0.3 mm, a wall thickness of 0.2 mm, and a length of 1 mm is obtained.

[0146] After testing, the membrane flux of the hollow adsorbent with a hollow tube provided in this embodiment is 222L / (m 2 h).

[0147] Example 4

[0148] The preparation method of the hollow adsorbent and adsorption device provided in this embodiment is basically the same as that in embodiment 1, except that:

[0149] In step 3), the vibration degassing time is replaced by 10 s from 30 s; a hollow adsorbent having a hollow tube body with an inner diameter of 0.3 mm, a wall thickness of 0.1 mm, and a length of 1 mm is obtained.

[0150] After testing, it was found that the internal pores provided in this embodiment were rich, and the mesopores on the outer surface, the finger-like pores penetrating the hollow adsorbent, and the micropores outside the adsorbent particles constituted a multi-dimensional pore system of the hollow adsorbent. The membrane flux of the hollow adsorbent was 210L / (m 2 h).

[0151] Example 5

[0152] The preparation method of the hollow adsorbent and adsorption device provided in this embodiment is basically the same as that in embodiment 1, except that:

[0153] 4. Pump the casting liquid through a 200-mesh filter to filter out large particles of impurities in the casting liquid. The casting liquid is spun into adsorbent filaments through a spinning head. The spinning head is a coaxial circular tube with four layers of holes (two core liquid holes and two casting liquid holes). The spinning head temperature is 60°C. Water is introduced in the middle as the core liquid. The flow rate ratio of the inner core liquid, inner spinning, outer core liquid and outer spinning is 1:2:4:10. The air bath height is 30 cm. The inner diameter of the inner layer of the filament is 0.2 mm, the wall thickness is 0.1 mm, the inner diameter of the outer layer is 0.4 mm, and the wall thickness is 0.1 mm. The spun filaments are solidified in water at 60°C, and the membrane filaments are washed five times with water of equal mass, and then soaked in 50% glycerol aqueous solution for 2 hours. The adsorbent wire is cut into particles to obtain a hollow adsorbent having two hollow tubes, wherein the inner diameter of the inner hollow tube is 0.2 mm, the wall thickness is 0.1 mm, and the inner diameter of the outer hollow tube is 0.4 mm, the wall thickness is 0.1 mm, and the length is 1 mm. Figure 4 As shown, there is a contact area between the inner hollow tube body and the outer hollow tube body, the arc length of the contact area of ​​the hollow tube cross section is L1, and the overall arc length of the hollow tube cross section is L2, satisfying L1:L2=40%.

[0154] After testing, the membrane flux of the hollow adsorbent provided in this embodiment is 190L / (m 2 h).

[0155] Example 6

[0156] The preparation method of the hollow adsorbent and the adsorption device provided in this embodiment comprises the following steps:

[0157] 1) Add aluminum-based adsorbent (D50 is 0.5 μm) and N,N-dimethylacetamide into a reaction kettle at a mass ratio of 30:100, mix them thoroughly at room temperature to obtain a mixed solution, stir the mixture at a stirring rate of 100 rpm, and evacuate the mixture at 4 kPa for 2 h to obtain a degassed suspension;

[0158] 2) Add polyethersulfone, polyvinyl alcohol and acetic acid to the degassed suspension in a mass ratio of 5:100, 0.1:100 and 0.5:100 to the adsorbent material, respectively; stir at 25° C. and 100 rpm until the suspension is completely dissolved to obtain a precast membrane solution;

[0159] 3) Degas the precasting liquid by vibrating it at a frequency of 100 Hz for 10 seconds, and then degas it under vacuum at 1 kPa for 1 hour to obtain a casting liquid;

[0160] 4) Pump the casting liquid through a 200-mesh filter to filter out large particles of impurities in the casting liquid, and then spin the adsorbent filaments through a spinning head. The spinning head temperature is 60°C, and water is introduced in the middle as the core liquid. The flow rate ratio of the core liquid to the spinning is 1:1. The air bath height is 30 cm. The filaments are single-hole circular tubes with an inner diameter of 0.3 mm and a wall thickness of 0.1 mm. The spun filaments are solidified in 60°C water, and the membrane filaments are washed five times with equal mass water, and then soaked in a 50% glycerol aqueous solution for 2 hours. Cut the adsorbent filaments into particles to obtain a hollow adsorbent with an inner diameter of 0.3 mm, a wall thickness of 0.1 mm, and a length of 3 mm.

[0161] 5) Load the hollow adsorbent into the empty adsorption column three times, flush it with water from top to bottom at a speed of 30m / s for 10min each time, compact and flatten the hollow adsorbent to obtain the adsorption column.

[0162] After testing, the membrane flux of the hollow adsorbent with a hollow tube provided in this embodiment is 185L / (m 2 h).

[0163] Example 7

[0164] The preparation method of the hollow adsorbent and adsorption device provided in this embodiment is basically the same as that in embodiment 1, except that:

[0165] In step 4), the spacing between the inner and outer walls of the spinning head treated by spinning is 0.03 mm, and the hollow adsorbent with an inner diameter of 0.3 mm, a wall thickness of 0.02 mm, and a length of 0.1 mm is obtained by cutting.

[0166] After testing, the membrane flux of the hollow adsorbent with a hollow tube provided in this embodiment is 295L / (m 2 h).

[0167] Example 8

[0168] The preparation method of the hollow adsorbent and adsorption device provided in this embodiment is basically the same as that in embodiment 1, except that:

[0169] In step 1), the D50 of the adsorbent material is 1.2 μm; a hollow adsorbent having an inner diameter of 0.3 mm, a wall thickness of 0.1 mm, and a length of 1 mm and a hollow tube is obtained.

[0170] After testing, the membrane flux of the hollow adsorbent with a hollow tube provided in this embodiment is 89L / (m 2 h).

[0171] Example 9

[0172] The preparation method of the hollow adsorbent and adsorption device provided in this embodiment is basically the same as that in embodiment 1, except that:

[0173] In step 3), the mass ratio of the aluminum-based adsorbent to polyvinyl pyrrolidone is 100:3.5, and the mass ratio of the aluminum-based adsorbent to oxalic acid is 100:0.03; a hollow adsorbent having an inner diameter of 0.3 mm, a wall thickness of 0.1 mm, and a length of 1 mm and a hollow tube is obtained.

[0174] After testing, the membrane flux of the hollow adsorbent with a hollow tube provided in this embodiment is 65L / (m 2 h).

[0175] Example 10

[0176] The preparation method of the hollow adsorbent and adsorption device provided in this embodiment is basically the same as that in embodiment 1, except that:

[0177] In step 4), the 50 wt % glycerol aqueous solution is replaced with a 35 wt % glycerol aqueous solution; a hollow adsorbent having an inner diameter of 0.3 mm, a wall thickness of 0.1 mm, and a length of 1 mm and a hollow tube is obtained.

[0178] After testing, the membrane flux of the hollow adsorbent with a hollow tube provided in this embodiment is 90L / (m 2 h).

[0179] Embodiment 11

[0180] The preparation method of the hollow adsorbent and adsorption device provided in this embodiment is basically the same as that in embodiment 1, except that:

[0181] In step 5), the inner diameter is 0.3 mm, the wall thickness is 0.1 mm, the length is 1 mm, and the membrane flux is 300 L / (m 2 h) is loaded into an empty adsorption column at one time to obtain an adsorption column.

[0182] After testing, the membrane flux of the hollow adsorbent with a hollow tube provided in this embodiment is the same as that in Example 1.

[0183] Comparative Example 1

[0184] The preparation method of the hollow adsorbent and adsorption device provided in this comparative example comprises the following steps:

[0185] 1) Add aluminum-based adsorbent (D50 is 0.5 μm), N-methylpyrrolidone and polyvinylidene fluoride into a reaction kettle at a mass ratio of 1:2:0.11, stir at 80°C until mixed completely, and vacuum degas to prepare a casting solution;

[0186] 2) Pump the casting liquid through a 300-mesh filter to filter out large particles of impurities in the casting liquid, and then spin the adsorbent filaments through a spinning head. The spinning head temperature is 60°C, and water is introduced in the middle as the core liquid. The flow rate ratio of the core liquid and the spinning is 1:1. The air bath height is 30 cm. The filaments are single-hole circular tubes with an inner diameter of 0.3 mm and a wall thickness of 0.3 mm. The spun filaments are solidified in 60°C water, and the membrane filaments are washed five times with equal mass water, and then soaked in a 50% glycerol aqueous solution for 2 hours. Cut the adsorbent filaments into particles to obtain a hollow adsorbent with an inner diameter of 0.3 mm, a wall thickness of 0.3 mm, and a length of 1 mm with a hollow tube body.

[0187] 3) Load the hollow adsorbent into the empty adsorption column in 5 times, flush it with water from top to bottom at a speed of 10m / s for 30min each time, compact and flatten the hollow adsorbent to obtain the adsorption column.

[0188] Comparative Example 2

[0189] The preparation method of the hollow adsorbent and adsorption device provided in this comparative example is basically the same as that in Example 1, except that:

[0190] In step 2), the mass ratio of polyvinylidene fluoride to the adsorbent material is 3:100;

[0191] In step 3), the precasting liquid is vibrated and degassed at a frequency of 50 Hz for 0 s, and then vacuum degassed at 2 kPa for 1 h to obtain a casting liquid.

[0192] A hollow adsorbent having a hollow tube body with an inner diameter of 0.3 mm, a wall thickness of 0.1 mm, and a length of 1 mm was obtained.

[0193] Test Case

[0194] 1. Static adsorption test

[0195] The hollow adsorbents provided in all the embodiments and comparative examples were tested, comprising the following steps:

[0196] Take lithium-containing brine with high magnesium-lithium ratio for testing, Li + The concentration is 326ppm, Mg 2+ The concentration is 92910ppm, and the mass ratio of magnesium to lithium in the brine is 285:1.

[0197] Weigh 10g of hollow adsorbent, adsorb at a mass ratio of 1:50 between the hollow adsorbent and brine at room temperature, stir at 300rpm, adsorb for 20min, test the adsorption rate (adsorption rate = adsorbed lithium amount / adsorption time); continue adsorption for 70min, calculate the adsorption capacity and adsorbent utilization (adsorbent utilization = adsorption capacity / adsorbent powder adsorption capacity, powder adsorption capacity is 11.25mg / g); then filter and rinse, with 200mL of rinsing water. After elution, desorb with pure water at a solid-liquid ratio of 1:50, stir at 500rpm, temperature at 40℃, desorb for 20min, test the adsorption rate (adsorption rate = desorbed lithium amount / desorption time), and continue desorption for 100min. See Table 1 for specific test results.

[0198] 2. Adsorption column adsorption test

[0199] The adsorption columns provided in all the embodiments and comparative examples were tested, including the following steps:

[0200] Take lithium-containing brine with high magnesium-lithium ratio for testing, Li + The concentration is 326ppm, Mg 2+ The concentration is 92910ppm, and the mass ratio of magnesium to lithium in the brine is 285:1. The adsorption column volume is 450ml, and the filling volume is 400ml. The brine adsorption rate is 8BV / h, the adsorption amount is 12BV, and the time is 1.5h; the pure water elution rate is 8BV / h, and the elution to the magnesium-lithium ratio is 1.5, and the elution water consumption is calculated; the pure water desorption rate is 8BV / h, the desorption amount is 5BV, and the time is 0.625h. Calculation of lithium extraction efficiency by column adsorption:

[0201] Lithium extraction efficiency = total amount of qualified liquid lithium in a single column / total time of a single cycle

[0202] The specific test results are shown in Table 1.

[0203] Table 1

[0204]

[0205]

[0206] As shown in Table 1, the adsorption rate of the hollow adsorbent provided in Examples 1-11 is not less than 8.1 mg / h, the desorption rate is not less than 8.0 mg / h, the adsorption capacity is not less than 8.5 mg / g, the adsorbent utilization rate is not less than 86.8, the adsorption rate after 50 cycles is not less than 7.6 mg / min, the elution water consumption per mg of Li is not more than 355 ml when the magnesium-lithium ratio of the analytical solution is 1.5, and the lithium extraction efficiency is not less than 788. It shows that the hollow adsorbent provided in Examples 1-11 of the present invention has excellent cycle stability, adsorption efficiency and adsorption utilization compared with the hollow adsorbent provided in Comparative Examples 1 and 2, and the water consumption is low when used for lithium extraction from brine.

[0207] Among them, Example 2 uses more pore-forming agent than Example 1, which causes the bulk density and packing density to be reduced, while the pulverization rate is increased, and the impact on other indicators is small; the wall thickness of the sample prepared in Example 3 is greater than that in Example 1, which causes the membrane flux and adsorption and desorption rate to be reduced; the vibration time in Example 4 is shortened, resulting in a decrease in the bulk density, packing density and membrane flux; Example 5 prepares a double-layer hollow membrane with a higher packing density and a lower pulverization rate, and a higher lithium extraction efficiency; the size of the hollow adsorbent provided in Example 7 is inconsistent with that in Example 1, which reflects that the preferred size of the hollow adsorbent is an inner pore diameter of 0. 1-0.5mm, the wall thickness is 0.05-0.2mm, and the length is 0.5-3mm; the particle size D50 of the adsorbent material in the hollow adsorbent provided by Example 8 is different from that in Example 1, which shows that the effect is better when the particle size D50 of the adsorbent material is in the range of 0.01-1μm; compared with Example 1, Example 9 shows that the mass relationship between each component affects the performance of the hollow adsorbent; compared with Example 1, Example 10 shows the effect of 50wt% glycerol on the performance of the hollow adsorbent; compared with Example 1, Example 11 shows that loading the hollow adsorbent in stages can further improve the adsorption performance of the hollow adsorbent.

[0208] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A hollow adsorbent, characterized in that: comprising at least one hollow tube, wherein the hollow tube comprises an adsorbent material; The wall thickness of the hollow tube is 0.02-0.2 mm, and the powdering rate is ≤0.5%.

2. The hollow adsorbent according to claim 1, characterized in that: The inner diameter of the hollow tube is 0.01-2 mm, and the length is 0.1-5 mm.

3. The hollow adsorbent according to claim 1 or 2, characterized in that: The hollow adsorbent includes N hollow tubes which are arranged in sequence, 2≤N≤5, there is a contact area between two adjacent hollow tubes, the arc length of the contact area of ​​the hollow tube cross section is L1, the overall arc length of the hollow tube cross section is L2, and L1:L2=5%~50% is satisfied.

4. The hollow adsorbent according to claim 2, characterized in that: The inner diameter of the hollow tube is 0.1-0.5 mm, the wall thickness is 0.05-0.2 mm, and the length is 0.5-3 mm.

5. The hollow adsorbent according to any one of claims 1 to 4, characterized in that: The bulk density of the adsorbent material is 0.4-0.5 g / mL; And / or, the D50 of the adsorbent material is 0.01-1 μm.

6. The hollow adsorbent according to any one of claims 1 to 5, characterized in that: The membrane flux of the hollow adsorbent is 100-300L / (m 2 h).

7. The hollow adsorbent according to any one of claims 1 to 6, characterized in that: The hollow adsorbent also includes a pore-forming agent, an additive, and a binder; The mass ratio of the adsorbent material to the pore-forming agent is 100:(0.1-3); and / or, the mass ratio of the adsorbent material to the additive is 100:(0.05-0.5); And / or, the mass ratio of the adsorbent material to the binder is 100:(5-14).

8. The hollow adsorbent according to claim 7, characterized in that: The adsorbent material includes at least one of an aluminum-based adsorbent, a titanium-based adsorbent, and a manganese-based adsorbent; And / or, the adhesive comprises at least one of homopolymer polyvinylidene fluoride, copolymer polyvinylidene fluoride, polyether sulfone, and polyvinyl butyral; And / or, the pore-forming agent includes at least one of polyvinyl pyrrolidone, polyvinyl alcohol, lithium chloride and sodium chloride; And / or, the additive includes at least one of oxalic acid, citric acid, and acetic acid.

9. A method for preparing the hollow adsorbent according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) subjecting a mixed solution including an adsorbent material and an organic solvent to a first stirring treatment, and then subjecting the mixed solution to a first exhaust treatment to obtain a degassed suspension; 2) performing a second stirring treatment on the second mixed liquid including the degassed suspension to obtain a precast membrane liquid; 3) vibrating the precasting liquid, and then performing a second vacuuming process to obtain a casting liquid; 4) The casting solution is subjected to hollow molding treatment in sequence, and cut to obtain the hollow adsorbent.

10. The preparation method according to claim 9, characterized in that: The second mixed solution also includes a binder, a pore former, and an additive; The rotation speed of the first stirring treatment is 100-800 rpm; And / or, the pressure of the first vacuum treatment is 0.5-4KPa, and the time is 1-2h; And / or, the second stirring treatment has a rotation speed of 100-800 rpm and a temperature of 25-80° C.; And / or, the frequency of the vibration treatment is 25-100 Hz, and the time is 10-40 s; And / or, the pressure of the second vacuum treatment is 0.5-4 KPa, and the time is 1-2 hours.

11. The preparation method according to claim 9 or 10, characterized in that: The hollow molding process comprises the following steps: The filtered casting liquid and core liquid are used to prepare adsorbent filaments by a spinning head. The flow rate ratio of the core liquid to the filtered casting liquid is in the range of (1-10):1, and the air bath height is 5-30 cm. The filaments are then coagulated in a coagulation solvent at 25-80° C. to obtain an intermediate.

12. The preparation method according to claim 11, characterized in that: In step 4), the hollow molding process further includes washing, and the washing includes the following steps: The intermediate obtained by the hollow molding treatment is washed with water and then immersed in a 50 wt. % to 70 wt. % glycerol aqueous solution for 2 to 6 hours.

13. An adsorption device, characterized in that: The invention comprises the hollow adsorbent described in any one of claims 1 to 8 or the hollow adsorbent prepared by the preparation method described in any one of claims 9 to 12.

14. The adsorption device according to claim 13, characterized in that: The packing density of the hollow adsorbent in the adsorption device is not less than 0.38 g / mL.

15. The adsorption device according to claim 14, characterized in that: Prepared by a method comprising the following steps: The hollow adsorbent is loaded into the cavity of the adsorption device in several batches, and water is passed through the cavity at a flow rate of 10-30 m / s for compaction for 10-30 minutes after each loading.

16. The adsorption device according to claim 15, characterized in that: The hollow adsorbent is loaded into the cavity of the adsorption device in 3-5 batches.